The Old and the New in Prekallikrein Deficiency: Historical Context and a Family from Argentina with PK Deficiency due to a New Mutation (Arg541Gln) in Exon 14 Associated with a Common Polymorphysm (Asn124Ser) in Exon 5 - Girolami, Antonio; Vidal, Josè; Salagh, Marcela; Gervan, Nora; Parody, Maria; Peroni, Edoardo; Sambado, Luisa; Guglielmone, Hugo (Seminars in Thrombosis and Hemostasis, 2014)
Prekallikrein (PK) is one of the clotting factors involved in the contact phase of blood. PK has an important historical role as its deficiency state represents the second instance of a clotting defect without bleeding manifestations, the first one being factor XII deficiency. PK deficiency is a rare clotting disorder. Moreover, only 11 patients have been investigated so far by molecular biology techniques. In this article, we briefly review some of the history around PK and also present some recent data on a newly identified family from Argentina suffering from PK deficiency. Two patients are homozygous whereas other family members are heterozygous. PK activity and antigen are 1% of normal in the homozygotes and around 60 to 70% of normal in the heterozygotes. As expected, all patients are asymptomatic of bleeding or thrombosis presentations. However, the two homozygotes showed essential hypertension. The PK deficiency in this family is due to a new mutation (Arg541Gln) in exon 14. The defect segregates together with a known polymorphism, Asn124Ser, in exon 5. The significance of the presence of hypertension in the two homozygotes is discussed in view of the extra coagulation effects of PK on vasodilation, vessel permeability, and the control of blood pressure. Structure function analysis indicates that the substitution of Arg with Gln probably impedes the transmembrane diffusion of the molecule, which therefore cannot be secreted in the homozygotes. The presence of hypertension in patients with PK deficiency has been previously reported in some but not all patients. Future research activities will probably concentrate on the effect of PK and other contact phase factors on the vascular system.
Keywords: prekallikrein deficiency; contact phase; hypertension; blood coagulation